IGSF1 mutations are the most frequent genetic aetiology of thyrotropin deficiency. Issue 6 (3rd November 2022) - Fourneaux, Rachel; Reynaud, Rachel; Mougel, Gregory; Castets, Sarah; Bretones, Patricia; Dauriat, Benjamin; Edouard, Thomas; Raverot, Gerald; Barlier, Anne; Brue, Thierry; Castinetti, Frederic; Saveanu, Alexandru
Abstract: Design: Thyroid-stimulating hormone deficiency (TSHD) is a rare disease. It may be isolated, secondary to abnormalities of genes involved in TSH biosynthesis, or associated with other pituitary deficits or abnormalities of genes involved in pituitary ontogenesis. Several genes are involved in thyrotroph development and function. Objective: Our aim was to determine the genetic causes of TSHD, either isolated (ITSHD) or associated with somatotroph deficiency (TSHD-GHD), in the cohort of patients from the GENHYPOPIT network. Methods: Next-generation sequencing (NGS) analyses were performed as a panel of genes on a cohort of patients with non-syndromic ITSHD or TSHGHD. The variants were classified according to the American College of Medical Genetics classification reviewed by the NGS-Diag network and correlated with the phenotype. Class 3, 4, and 5 single-nucleotide variants were checked by Sanger sequencing and copy number variants by multiplex ligation-dependent probe amplification (MLPA). Results: A total of 64 index cases (22 ITSHD and 42 TSHD-GHD) were included in this cohort. A genetic cause was identified in 26.5% of patients, with 36.3% in the ITSHD group (variants in TSHβ and IGSF1 ) and 21.4% in TSHD-GHD (variants in IGSF1, TSHβ, TRHR, GH1, POU1F1, and PROP1 ). Among the pathogenic and likely pathogenic variants identified, 42% were in IGSF1, including six not previously reported. Conclusion: Our results show that IGSF1 variants represent the most frequent aetiology of TSH deficiency. Despite a systematic NGS approach and the identification of new variants, most patients remain without a molecular diagnosis. Larger scale studies, such as exome or genome studies, should be considered in the future.